On the Optimal Design of Triple Modular Redundancy Logic for SRAM-based FPGAs - Kastensmidt, F. Lima; Sterpone, L.; Carro, L.; Reorda, M. Sonza (Design, Automation and Test in Europe, 2005)
Triple Modular Redundancy (TMR) is a suitable fault tolerant technique for SRAM-based FPGA. However, one of the main challenges in achieving 100% robustness in designs protected by TMR running on programmable platforms is to prevent upsets in the routing from provoking undesirable connections between signals from distinct redundant logic parts, which can generate an error in the output. This paper investigates the optimal design of the TMR logic (e.g., by cleverly inserting voters) to ensure robustness. Four different versions of a TMR digital filter were analyzed by fault injection. Faults were randomly inserted straight into the bitstream of the FPGA. The experimental results presented in this paper demonstrate that the number and placement of voters in the TMR design can directly affect the fault tolerance, ranging from 4.03% to 0.98% the number of upsets in the routing able to cause an error in the TMR circuit.